"Moulding his human personality": Personality Change and Formation to Priesthood in the Catholic Church. Issue 2 (November 2019) - Selvam, Sahaya G.
The official documents on formation to priesthood in the Catholic Church encourage the use of personality psychology. Generally, the documents understand human personality to be dynamic. What does this mean in the light of the contemporary debate on the psychology of personality change? This article attempts to summarize the salient features of this debate, pointing out its relevance to priestly formation. Supporting a "whole-person model" of personality as proposed by Dan McAdams, the article considers the possibility of personality change at some levels in the context of religious experience facilitated by seminary formation. This article is also aimed at enlightening formation guides to make an informed decision in the choice of appropriate models of personality in the accompaniment of their candidates.